Analysis of the Influence of Culture, Policy, and Practice Index on the Quality of Inclusive School Education in South Kalimantan - Amka, Amka; Mirnawati, Mirnawati; Damastuti, Eviani (Department of Special Education, 2023)
This study aims to measure the effect of the index of policy, culture, and teaching practice on the quality of inclusive education in South Kalimantan. This study uses a quantitative approach with a survey method. The population in this study were Special Education Teachers, Classroom Teachers, Staff, Principals, and Parents providing inclusive education in South Kalimantan. The sampling technique used non-probability sampling with incidental sampling using the Slovin formula. Primary data was obtained by using a closed questionnaire. The data were analyzed using the Structural Equation Modeling analysis tool from the AMOS statistical software package through two techniques, namely Confirmatory Factor Analysis and Regression Weight. The results showed that the index of developing inclusive practices had a significant effect on the quality of inclusive education. while the index of creating an inclusive culture and producing inclusive policies has no significant effect on the quality of inclusive education.